(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This article considers the heat and humidity change laws during the year at the highways foot and the water-heat regime processes in it. The heat and humidity order at the road foot was studied, and the research results on the specific heat capacity of the soil, the freezing depth depends on its salinity, elevation, salt amount and quality